Kinderbetreuung und Beschäftigung von Frauen - Eine Analyse für Kärnten - Rodiga-Laßnig, Petra; Aigner-Walder, Birgit (Wirtschaft und Gesellschaft, 2014)
The demographic change in the sense of the ageing of the population is often seen as a threat for economic development (e.g. labour market shortage, provision and financing of social security). Concerning the labour market, an extended participation of women is often mentioned as one of various measures to cover the expected shortage in labour supply caused by the pension waves of the baby-boom generation. In Austria, Carinthia - the most southern region - is especially affected by the demographic change, with an already decreasing population and one of the highest shares of people aged 60 and more. Additionally, the labour market participation of women in Carinthia is lower than the Austrian average. Within the paper we analyse the relationship between the provision of childcare and labour market participation of women. The results of a representative survey of women in Carinthia aged between 20 and 49 years are presented. The paper shows highly significant differences in the employment behaviour of women depending on children as well as the importance of institutional childcare services to increase the labour market participation of women.